Comparison Between the Japanese Orthopaedic Association (JOA) Score and Patient-Reported JOA (PRO-JOA) Score to Evaluate Surgical Outcomes of Degenerative Cervical Myelopathy. Issue 5 (June 2022) - Oshima, Yasushi; Takeshita, Katsushi; Kato, So; Doi, Toru; Matsubayashi, Yoshitaka; Taniguchi, Yuki; Nakajima, Koji; Oguchi, Fumihiko; Okamoto, Naoki; Sakamoto, Ryuji; Tanaka, Sakae
Study Design: A retrospective cohort study. Objective: To investigate whether the Japanese Orthopaedic Association (JOA) score can be used for patients with degenerative cervical myelopathy as a patient-reported outcome (PRO) through the JOA written questionnaire. Methods: A total of 75 patients who underwent posterior decompression surgery for degenerative cervical myelopathy were reviewed. Patients responded to questionnaires including PRO-JOA, EuroQOL-5D, Neck Disability Index, and Short Form-12 preoperatively and at >12 months postoperatively. Spearman's rho and Bland-Altman analyses were used to investigate the correlations. Results: Preoperative JOA and PRO-JOA scores were 10.8 and 10.6, respectively, with Spearman's rho of 0.74. Similarly, postoperative JOA and PRO-JOA scores were 13.3 and 12.9, respectively, with Spearman's rho of 0.68. However, the recovery rates for JOA and PRO-JOA scores were 42% and 27%, respectively, with Spearman's rho of 0.45. Compared with other PROs, JOA and PRO-JOA scores were moderately correlated. The minimum clinically important difference was 2.5 for JOA score, 3.0 for PRO-JOA score, 42% for JOA recovery rate, and 33% for PRO-JOA recovery rate. Bland-Altman analyses revealed that limits of agreement were −4.3 to 4.7, −3.4 to 4.3, and −75% to 106% for the preoperative score, postoperative score, and recovery rate, respectively. Conclusion: PRO-JOA score can also be used as a disease-specific scoring measure instead of JOA score. However, although both measures demonstrate a similar trend as a group analysis, PRO-JOA and JOA scores should be regarded as different outcomes.